2009
DOI: 10.1897/08-324r.1
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range transport of organic chemicals in the environment

Martin Scheringer

Abstract: Abstract-The long-range transport (LRT) of organic chemicals in the environment is reviewed, with particular focus on the role of environmental fate and transport models and the relationship between model results and field data. Results from generic multimedia box models, spatially resolved multimedia box models, and atmospheric transport models are highlighted, including conceptual investigations of cold-trap effect and global fractionation as well as results for particular chemicals, such as hexachlorocycloh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 152 publications
(224 reference statements)
0
55
0
1
Order By: Relevance
“…[11][12][13][14] These studies have highlighted the need for improved understanding of the fate and transport of aerosolassociated organic contaminants in the global environment. 1 In 2001 we found BDEs associated with ice algae, phytoplankton, and krill (Euphausia superba) along the western Antarctic Peninsula, 15 and BDEs have also been found in Antarctic fish and penguins, 16,17 moss and lichens, 18 and in sediments and benthic organisms in the vicinity of McMurdo research station in Antarctica. 19 This latter paper indicated that local inputs from research activities may be an important source of BDEs to the Antarctic marine environment.…”
Section: Introductionmentioning
confidence: 89%
“…[11][12][13][14] These studies have highlighted the need for improved understanding of the fate and transport of aerosolassociated organic contaminants in the global environment. 1 In 2001 we found BDEs associated with ice algae, phytoplankton, and krill (Euphausia superba) along the western Antarctic Peninsula, 15 and BDEs have also been found in Antarctic fish and penguins, 16,17 moss and lichens, 18 and in sediments and benthic organisms in the vicinity of McMurdo research station in Antarctica. 19 This latter paper indicated that local inputs from research activities may be an important source of BDEs to the Antarctic marine environment.…”
Section: Introductionmentioning
confidence: 89%
“…They allow to estimate and to predict phase partitioning, transport, and transformation of chemicals at local to global scales (Scheringer, 2009). A number of platforms are available to model the fate of conventional chemical compounds in different environmental compartments, such as soils, surface-and groundwaters.…”
Section: Nanomaterials In the Aquatic Environment: General Consideratmentioning
confidence: 99%
“…The physical and chemical characteristics of these substances make possible that a POP released anywhere, can eventually grow to anywhere in the world. These pesticides are propagated by evaporation into the atmosphere from warmer regions of the world -tropical countries, which is precisely where they are most commonly used-to the cooler regions, where they are deposited by condensation (Scheringer, 2009). Evaporation rates in these cold regions of the planet are very low, therefore, such substances are "trapped" there, and deposited in living organisms (Scheringer, 2009).…”
Section: Environmentally Persistent Pesticidesmentioning
confidence: 99%
“…These pesticides are propagated by evaporation into the atmosphere from warmer regions of the world -tropical countries, which is precisely where they are most commonly used-to the cooler regions, where they are deposited by condensation (Scheringer, 2009). Evaporation rates in these cold regions of the planet are very low, therefore, such substances are "trapped" there, and deposited in living organisms (Scheringer, 2009). Anyhow, in contrast to expectations, the levels of POPs in tropical countries are similar to those found in the coolest regions (Weber et al, 2008).…”
Section: Environmentally Persistent Pesticidesmentioning
confidence: 99%